2013
DOI: 10.3390/molecules18089382
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Mediate Isoalantolactone-Induced Apoptosis in Human Prostate Cancer Cells

Abstract: Isoalantolactone, a medicinal plant-derived natural compound, is known to induce apoptosis in various cancer cell lines. However, its effect on apoptosis in prostate cancer cells has not been addressed. Thus, we examined the effects of isoalantolactone on prostate cancer cells. It was found that isoalantolactone inhibits growth of both androgen-sensitive (LNCaP) as well as androgen-independent (PC3 and DU-145) prostate cancer cells in a dose-dependent manner. Furthermore, our results indicate that isoalantolac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 39 publications
1
48
0
Order By: Relevance
“…Prostate cancer (PC), an androgen-sensitive cancer, is one of the most common malignancies among males in the United States and western world (1,2). Recently, 233,000 new PC cases are reported by American Cancer Society statistics in 2014 and it is estimated that about 29,480 patients are expected to die from it (3).…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer (PC), an androgen-sensitive cancer, is one of the most common malignancies among males in the United States and western world (1,2). Recently, 233,000 new PC cases are reported by American Cancer Society statistics in 2014 and it is estimated that about 29,480 patients are expected to die from it (3).…”
Section: Introductionmentioning
confidence: 99%
“…The regulation of apoptosis is, therefore, the most important in the treatment of cancer (Fulda, 2010;Lawen, 2003;Reed, 2002). Accumulated evidences indicated that the most of chemotherapeutic agents halt tumor cells proliferation via induction of apoptosis (Rasul et al, 2013a;Rasul et al, 2013b). TBMS1-induced cell death could be associated with apoptosis and necrosis (Kanduc et al, 2002;Kerr et al, 1972).…”
Section: Resultsmentioning
confidence: 99%
“…It also induced apoptosis in both androgen-sensitive (LNCaP) as well as androgenindependent (PC3 and DU-145) prostate cancer cells with the generation of ROS and dissipation of MMP (Dcm; ref. 136). Alantolactone induced apoptosis accompanied by ROS generation and mitochondrial transmembrane potential dissipation (49,137).…”
Section: Targeting Cancer Cells By Ros-mediated Apoptosis Pathwaymentioning
confidence: 99%